Factors Influencing Mortality of Thoracic Aortic Surgery in The Third World Country - Diansari, Rienna; Aligheri, Dicky; Herlambang, Bagus; Wicaksono, Sony Hilal; Mendel, Brian; Yaniarti, Dian; Alkatiri, Amir Aziz; Andriantoro, Hananto; Adiarto, Suko (The Indonesian Heart Association, 2025)
In “Factors Influencing Mortality of Thoracic Aortic Surgery in the Third World Country” (Indonesian Journal of Cardiology, 44(2), 41-52. https://doi.org/10.30701/ijc.1494), there are several errors noted.An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1494. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.An error also appears in the affiliations section. In the original article, the affiliation for author Brian Mendel was incorrectly displayed as “Department of Cardiology & Vascular Medicine, Faculty of Medicine, Universitas Indonesia, Jakarta, Indonesia”. The affiliation has been corrected to “Sultan Sulaiman Government Hospital, Serdang Bedagai, Sei Rampah, Indonesia”.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1494